Fermentasi Air Kelapa Muda sebagai Atraktan Nyamuk Aedes aegypti - Devinta Lala; Suprijandani .; Nur Haidah (GEMA LINGKUNGAN KESEHATAN, 2018)
The case of dengue fever caused by Aedes aegypti female mosquitoes is still a problem in Indonesia because the case tends to increase every year. The purpose of study on the fermentation of young coconut water as a mosquito attractant is to determine whether there is any difference in the number of mosquitoes trapped by the fermentation of young coconut water concentration variation. The type of research conducted was a True Experiment, with the design ofpost test only control group. Research method was using trapping bottle provided with attractant with a concentration of 0% (control), 15%, 25%, and 35%. Location of research was done in Laboratorium Entomologi Kesehatan Lingkungan Politeknik Kesehatan Kemenkes RI Surabaya. Data were analyzed using Kruskal Wallis statistical test and advanced test of Mann Whitney. The result of Kruskall Wallis statistic test showed that there is significant difference (p 0,05) between control group and treatment group of variation of coconut water fermentation concentration to the number of trapped mosquitoes. Advanced tests of Mann Whitney showed that three concentration treatments (15%, 25%, and 35%) had the same potential because there is no significant difference. Higher mean rank values at the 15% coconut water fermentation concentration is because it has the ability of trapping mosquitos more compared to other concentration (25%, and 35%). Young coconut water fermentation has potential as an Aedes aegypti mosquito attractant. The use of young coconut water fermentation attractant is a method of controlling mosquito vectors that is environmentally friendly and inexpensive to use. Keywords : Aedes, Attractant, Fermented Young Coconut Water, Trapping